Integrated operation of steady-state long-pulse H-mode in Experimental Advanced Superconducting Tokamak. (1st July 2019) - Gong, X.; Garofalo, A.M.; Huang, J.; Qian, J.; Holcomb, C.T.; Ekedah, A.; Maingi, R.; Li, E.; Zeng, L.; Zhang, B.; Chen, J.; Wu, M.; et al.
Abstract: Recent Experimental Advanced Superconducting Tokamak (EAST) experiments have successfully demonstrated a long-pulse steady-state scenario with improved plasma performance through integrated operation since the last IAEA FEC in 2016. A discharge with a duration over 100 s using pure radio frequency (RF) power heating and current drive has been obtained with the required characteristics for future long-pulse tokamak reactors such as good energy confinement quality (H98y2 1.1) with electron internal transport barrier inside ρ < 0.4, small ELMs (frequency 100–200 Hz), and good control of impurity and heat exhaust with the tungsten divertor. The optimization of X -point, plasma shape, the outer gap and local gas puffing near the low hybrid wave (LHW) antenna were integrated with global parameters of B T and line-averaged electron density for higher current drive efficiency of LHW and on-axis deposition of electron cyclotron heating in the long-pulse operation. More recently, a high β P RF-only discharge ( β P 1.9 and β N 1.5, / n GW 0.80, f bs 45% at q 95 6.8) was successfully maintained over 24 s with improved hardware capabilities, demonstrating performance levels needed for the China Fusion Engineering Test Reactor steady-state operation. A higher energy confinement is observed at higher β P and with favorable toroidal field direction. Towards the next goal (⩾400 s long-pulse H-mode operations with 50% bootstrap current fraction) on EAST, an integrated control of the current density profile, pressure profile and radiated divertor will be addressed in the near future.